Is periodontal disease a reason or result for premature birth? - Turgut Demir; Gülnihal Emrem (Wolters Kluwer Medknow Publications, 2012)
Introduction: It is a known fact that there is a connection between periodontal disease and certain systemic conditions. Even though there are some contradictory results in the conducted studies, periodontal disease has been accepted as a risk factor affecting the negative terminations of pregnancy in recent years (premature birth [PB], low birth weight). This consideration is associated with a positive correlation between two conditions in some studies. The Hypothesis: Although there is such a relationship between periodontal disease and PB, the linking mechanism has not been explained as presence of the relation cannot reveal the cause-effect relationship. It should be discussed whether or not this positive connection is caused by the fact that periodontal disease is an independent risk factor for PB, or the change (hormonal, inflammatory) in the systemic condition in PB cases causes a risk for periodontal disease. Evaluation of the Hypothesis: The fact that in PB cases the changes in steroid hormone levels might increase the incidence and severity of periodontal disease as in pregnancy, or there could be a common risk factor that may cause both cases, has not been revealed yet and should be taken into consideration.